2009
DOI: 10.1128/aac.01660-08
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered R-Type Pyocin Is a Highly Specific and Sensitive Bactericidal Agent for the Food-Borne Pathogen Escherichia coli O157:H7

Abstract: Some strains of Pseudomonas aeruginosa produce R-type pyocins, which are high-molecular-weight phage tail-like protein complexes that have bactericidal activity against other Pseudomonas strains. These particles recognize and bind to bacterial surface structures via tail fibers, their primary spectrum determinant. R-type pyocins kill the cell by contracting a sheath-like structure and inserting their hollow core through the cell envelope, resulting in dissipation of the cellular membrane potential. We have ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 36 publications
1
107
0
Order By: Relevance
“…Similarly, the pts cluster required for the production of photorhabdicin in P. luminescens contains multiple fiber genes in the same location (10). Variation at the C terminus of fiber proteins created by DNA inversion or recombination, or replacement of the native fiber gene with one from a related strain, alters the spectrum of activity of the respective R-type bacteriocins (24,27,40). Recombination between the C-terminal domain of xnpH1 and tail fiber genes adjacent to xnpH1 in a subpopulation of cells could expand the range of xenorhabdicin activity and enhance the ability of X. nematophila to compete against other Xenorhabdus and Photorhabdus strains and possibility less related bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the pts cluster required for the production of photorhabdicin in P. luminescens contains multiple fiber genes in the same location (10). Variation at the C terminus of fiber proteins created by DNA inversion or recombination, or replacement of the native fiber gene with one from a related strain, alters the spectrum of activity of the respective R-type bacteriocins (24,27,40). Recombination between the C-terminal domain of xnpH1 and tail fiber genes adjacent to xnpH1 in a subpopulation of cells could expand the range of xenorhabdicin activity and enhance the ability of X. nematophila to compete against other Xenorhabdus and Photorhabdus strains and possibility less related bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…They are composed of an outer sheath, an inner tube, and associated tail fibers. R-type pyocins bind via tail fibers to lipopolysaccharide (LPS) receptors on the surface of sensitive bacteria (18,24,27,40). It has been shown that recombination of tail fiber proteins broadens R-type bacteriocin specificity (24).…”
mentioning
confidence: 99%
“…The soluble S-type is similar to colicins of E. coli and is composed of killing and immunity genes. While the R and F type are phage-derived and have different killing and resistance mechanisms, where both consist of only a killing component with no specified immunity that neutralizes the toxin but instead resist via alteration or absence of cell-surface receptors [2,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The generated chimeric tail fibers that formed active pyocins resulted from many trials of empirically chosen fusion sites between prf15 and portions of bacteriophage tail/spike fibers. The engineered fusions between N-terminal portions of the pyocin tail fiber and various C-terminal portions of the bacteriophage tail/spike fibers resulted in pyocin host range expansion from Pseudomonas to Yersinia and various E. coli strains [70,71]. Scholl et al further envisage that an unlimited amount of chimeric pyocins can be created based on the presence of a vast number and diversity of bacteriophage tail fibres combined with the application of phage display techniques.…”
Section: Pyocinsmentioning
confidence: 99%